Development of a sales information system to improve Batik Shop’s sales efficiency - Prijambodo , Bambang; Fajrin , Ahmad Miftah; Susila, Vikantya; Aziiza, Arizia Aulia (Keluwih: Jurnal Sains dan Teknologi, 2024)
Abstract—Batik is an indigenous cultural artifact of Indonesia that demands conservation. This study's batik establishment, Satrio Manah Batik, is located in Tulungagung and specializes in selling authentic Tulungagung batik. Sales for Satrio Manah Batik are conventional, and customers must physically visit the store. Satrio Manah Batik often makes custom orders, so it takes time for an appointment. The sales reach is limited to Tulungagung, and transactions are restricted to clients already acquainted with Satrio Manah Batik. Further, the antiquated book writing method must still be employed to record raw material stocks and sales reports. There needs to be a better record of the product inventory reports. It affects the calculations of monthly sales profits. Hence, this study was conducted to develop a sales information system to improve Satrio Manah Batik's sales efficiency. This research was developed using a waterfall model. The verification and validation results show that the system developed can meet customer needs. Customers can order custom batik by platform in a short time, which can increase the effectiveness of Batik Satrio Manah's sales. Keywords: sales information system, batik shop, efficiency Abstrak—Batik merupakan artefak budaya asli Indonesia yang perlu dilestarikan. Tempat usaha batik pada penelitian ini adalah Batik Satrio Manah, yang berlokasi di Tulungagung dan khusus menjual batik asli Tulungagung. Penjualan Batik Satrio Manah bersifat konvensional dan pelanggan harus mengunjungi toko secara fisik. Satrio Manah Batik sering membuat pesanan secara custom sehingga memerlukan waktu untuk membuat janji. Jangkauan penjualan Batik Satrio Manah hanya terbatas di Tulungagung, dan pembeliaan hanya dilakukan oleh pelanggan yang sudah mengenal Satrio Manah Batik. Selain itu, cara mencatat stok bahan baku dan laporan penjualan masih melakukan penulisan buku. Perlu adanya pencatatan laporan persediaan produk yang lebih baik. Hal ini mempengaruhi perhitungan keuntungan penjualan bulanan. Oleh karena itu, penelitian ini dilakukan untuk mengembangkan sistem informasi penjualan untuk meningkatkan efisiensi penjualan Batik Satrio Manah. Penelitian ini dikembangkan dengan menggunakan model waterfall. Hasil verifikasi dan validasi menunjukkan bahwa sistem yang dikembangkan dapat memenuhi kebutuhan pelanggan. Pelanggan dapat memesan batik custom melalui platform dalam waktu singkat sehingga dapat meningkatkan efektivitas penjualan Batik Satrio Manah. Kata kunci: sistem informasi penjualan, toko batik, efisiensi